Entre deux empires : le Maranhão dans l’Union ibérique (1614-1641) - Guida Marques (Nuevo mundo - Mundos Nuevos, 2010)
The conquest of the Marañón and Gran Pará takes place during the dynastic union of the crowns of Portugal and Castile, and the royal involvement prevents us from considering that conquest as an independent process on the borders of the Portuguese America. The practices of its actors reveal indeed how this conquest lies within the framework of the iberic union, suggesting also, with regard to the colonial experience of the 17th century, the connections between the Portuguese and Castilian empires.